Antiphospholipid antibodies and heart failure with preserved ejection fraction. The multicenter athero-aps study - Pastori, Daniele (2021)
Background. The prevalence of heart failure with preserved ejection fraction (HFpEF) in patients with antiphospholipid syndrome (APS) is unknown. Methods. A prospective multicenter cohort study including 125 patients was conducted: 91 primary APS (PAPS), 18 APS-SLE, and 16 carriers. HFpEF was diagnosed according to the 2019 European Society of Cardiology criteria: patients with ≥5 points among major and minor functional and morphological criteria including NT-ProBNP > 220 pg/mL, left atrial (LA) enlargement, increased left ventricular filling pressure. Results. Overall, 18 (14.4%) patients were diagnosed with HFpEF; this prevalence increased from 6.3% in carriers to 13.2% in PAPS and 27.8% in APS-SLE. Patients with HFpEF were older and with a higher prevalence of hypertension and previous arterial events. At logistic regression analysis, age, arterial hypertension, anticardiolipin antibodies IgG > 40 GPL (odds ratio (OR) 3.43, 95% confidence interval (CI) 1.09–10.77, p = 0.035), anti β-2-glycoprotein-I IgG > 40 GPL (OR 5.28, 1.53– 18.27, p = 0.009), lupus anticoagulants DRVVT > 1.25 (OR 5.20, 95% CI 1.10–24.68, p = 0.038), and triple positivity (OR 3.56, 95% CI 1.11–11.47, p = 0.033) were associated with HFpEF after adjustment for age and sex. By multivariate analysis, hypertension (OR 19.49, 95% CI 2.21–171.94, p = 0.008), age (OR 1.07, 95% CI 1.00–1.14, p = 0.044), and aβ2GPI IgG > 40 GPL (OR 8.62, 95% CI 1.23–60.44, p = 0.030) were associated with HFpEF. Conclusion. HFpEF is detectable in a relevant proportion of APS patients. The role of aPL in the pathogenesis and prognosis of HFpEF needs further investigation.